Untimely sacrifices : work and death in Finland - Funahashi, Daena Aki (Cornell University Press, 2023)
"Public health officials in Finland called occupational burnout a hazard of the new economy. A quick glance at the history of labor reveals how every economic regime comes with its own forms of dis-ease. This book, based on fieldwork in Finland, rethinks welfare and the political economy's emphasis on productive self-management by shifting the focus to what we are willing to sacrifice"--